A Survey on Security in Mobile Ad-Hoc Network and Solutions - Kumar, Navneet (International Journal of Computer Sciences and Engineering, 2025)
Ad hoc networks are temporary networks connection established for a small session, self-configured and organized networks without any fixed infrastructure. In Ad hoc networks, topology is dynamic as nodes communicate the network “on the fly” for a special purpose (such as transferring data between one computer to another). A Mobile Ad hoc network (MANET) is a dynamically arrangement of wireless Mobile nodes, communicate directly or using intermediate nodes without any predefined infrastructures. In the absence of any predefined infrastructures in networks become vulnerable to number of attacks and high level security becomes a major issue. In this survey paper, we first discuss the introduction to Mobile Ad hoc network. The second section discusses weaknesses or vulnerabilities in Mobile Ad hoc network. The third section discusses the types of attack in Mobile Ad hoc network. The fourth section discusses the security goals of Mobile Ad hoc network. Finally the last section discusses the security solutions to prevent the attacks and provide a high level security to Mobile Ad hoc networks.